2013
DOI: 10.1002/ceat.201300103
|View full text |Cite
|
Sign up to set email alerts
|

Limiting the Pollutant Content in the Sewage Sludge Producer Gas through Staged Gasification

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 66 publications
3
17
0
Order By: Relevance
“…Moreover, it can be observed that the ammonia released have the same kinetics trend for all feedstocks: production begins at 573 K ± 20 K, the maximum production was reached at about 823 K (SWWS 7% volume fraction, DWWS 6% volume fraction and WW 3% volume fraction). The same trend of ammonia release for WWS was described in earlier work by Hernandez et al [8]. WWS (S and D) are the most syngas pollutant release feedstock.…”
Section: Ammonia and Co Releasesupporting
confidence: 78%
See 3 more Smart Citations
“…Moreover, it can be observed that the ammonia released have the same kinetics trend for all feedstocks: production begins at 573 K ± 20 K, the maximum production was reached at about 823 K (SWWS 7% volume fraction, DWWS 6% volume fraction and WW 3% volume fraction). The same trend of ammonia release for WWS was described in earlier work by Hernandez et al [8]. WWS (S and D) are the most syngas pollutant release feedstock.…”
Section: Ammonia and Co Releasesupporting
confidence: 78%
“…The experimental setup used in this study was developed by Hernandez et al [8]. It has been established that this reactor is Abbreviation (Volumes are given in m 3 conversion rate consistent to study the pollutants and fuel gas release during pure steam gasification [5,8]. The equipment consists on a laboratory scale semi-batch gasifier.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…C1 gases, mainly CO and CO 2 , can be obtained from the gasification of wastes, coal, biomass and other feedstocks . Syngas is a complex mixture of gases, composed mainly of CO, CO 2 , and H 2 , which can be fermented by clostridia and other acetogens, mostly into acids and/or alcohols. Interestingly, those same gaseous substrates are found in some waste gases, among others in gaseous effluents from steel industries.…”
Section: Introductionmentioning
confidence: 99%